In Vitro Antioxidant and Anti-Glycation Activity of Resveratrol and Its Novel Triester with Trolox - Sebastiano Intagliata; Angelo Spadaro; Miriam Lorenti; Annamaria Panico; Edy A. Siciliano; Sabrina Barbagallo; Benito Macaluso; Shyam H. Kamble; Maria N. Modica; Lucia Montenegro (MDPI AG, 2020)
Resveratrol (RSV) is well known for its many beneficial activities, but its unfavorable physicochemical properties impair its effectiveness after systemic and topical administration; thus, several strategies have been investigated to improve RSV efficacy. With this aim, in this work, we synthesized a novel RSV triester with trolox, an analogue of vitamin E with strong antioxidant activity. The new RSV derivative (RSVTR) was assayed in vitro to evaluate its antioxidant and anti-glycation activity compared to RSV. RSVTR chemical stability was assessed at pH 2.0, 6.8, and 7.2 and different storage temperatures (5 °C, 22 °C, and 37 °C). An influence of pH stronger than that of temperature on RSVTR half-life values was pointed out, and RSVTR greatest stability was observed at pH 7.2 and 5 °C. RSVTR showed a lower antioxidant ability compared to RSV (determined by the oxygen radical absorbance capacity assay) while its anti-glycation activity (evaluated using the Maillard reaction) was significantly greater than that of RSV. The improved ability to inhibit the glycation process was attributed to a better interaction of RSVTR with albumin owing to its increased topological polar surface area value and H-bond acceptor number compared to RSV. Therefore, RSVTR could be regarded as a promising anti-glycation agent worthy of further investigations.